Modulation of adiposity and adipocyte inflammation by methanol extracts of Alpinia calcarata leaf in high-fat-diet induced-obese mice: Involvement of COX-2 and PPAR-γ - Imtiaz Ahmad; Maruful Hasan; Dipty Rani Bhowmik; Rahima Begum; Sourav Roy; Md Monirul Islam; Md Abdur Rahman Ripon; Mohammad Salim Hossain (Heliyon)
Obesity is a worldwide problem linked to several lifestyle disorders like diabetes, hypertension, heart failure, dyslipidaemias, asthma, etc. Finding a cure for obesity and its consequences is essential. Alpinia calcarata, a plant from the Zingiberaceae family, has been reported for several medicinal properties. The current study aimed to check out the role of Alpinia calcarata leaf in decreasing adiposity and adipocyte inflammation in high-fat diet-induced obese mice and understand the molecular principles underlying this occurrence. An in-silico test was done with more abounded compounds of Alpinia calcarata with adiposity and inflammatory genes. Moreover, methanol extract of Alpinia calcarata leaves were utilized to confirm the in-silico data in-vivo. High-fat diet induced-obese mice were treated with the extract at 200mg/kg-body weight dose. Body weight, organ weight, fat accumulation, serum cholesterol, serum triglyceride level, and liver function test were monitored as function of obesity. Alteration in the expression of IL-6, COX-2, MCP-1, PPARγ, TNFα, and GLUT-4 at transcript level were also studied. Our in-vivo results indicated that the plant extracts significantly (p < 0.05) decreased weight and accumulation of abdominal fat which was followed by a considerable reduction in total cholesterol and triglyceride levels. In agreement with the in-silico data, the extract was capable to reduce the mRNA expression of IL-6, COX-2, MCP-1, PPARγ, TNFα, and GLUT-4 which were consistent with the biochemical evidence; demonstrating the extract's capacity to attenuate adiposity and adipocyte inflammation. Taking it all together, it is noteworthy to report this novel function of A. calcarata leaf in reducing adiposity and adipocyte inflammation.